2011
DOI: 10.1103/physreve.84.036318
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear evolution and diffusion layer selection in electrokinetic instability

Abstract: In the present work, four nontrivial stages of electrokinetic instability are identified by direct numerical simulation (DNS) of the full Nernst-Planck-Poisson-Stokes system: (i) a stage of the influence of the initial conditions (milliseconds); (ii) one-dimensional (1D) self-similar evolution (milliseconds-seconds); (iii) a primary instability of the self-similar solution (seconds); (iv) a nonlinear stage with secondary instabilities. The self-similar character of evolution at moderately large times is confir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 18 publications
5
74
0
Order By: Relevance
“…In order to limit excessive grid refinement near membrane surfaces, the equations were solved with a dimensionless Debye length, λ = 10 −3 , far larger than a physically realistic value (i.e., ∼10 −4 ). Other studies [6,7,[15][16][17][18] employ similar dimensionless Debye length values, and as shown below, the simulation results are clearly qualitatively similar to the realistic phenomenon observed in the experiment.…”
Section: -2supporting
confidence: 69%
See 3 more Smart Citations
“…In order to limit excessive grid refinement near membrane surfaces, the equations were solved with a dimensionless Debye length, λ = 10 −3 , far larger than a physically realistic value (i.e., ∼10 −4 ). Other studies [6,7,[15][16][17][18] employ similar dimensionless Debye length values, and as shown below, the simulation results are clearly qualitatively similar to the realistic phenomenon observed in the experiment.…”
Section: -2supporting
confidence: 69%
“…2, we show simulated (SIM) and measured (EXP) ion concentrations at the outlet and on the symmetry plane of a system with aspect ratio w/d = 1. Note that there is a good match between simulation and experiment, and that the results lead to two conclusions: (1) In the Ohmic and limiting regimes, there is little concentration variation in the width (z) direction, indicating only minor 3D effects; (2) in the overlimiting regime, however, the concentration profile in the width direction exhibits characteristic features of electrokinetic instability (also known as "Rubinstein and Zaltzman" instability [7], often found in 2D quiescent solutions) [7,12,13,15,16]. In particular, there appear to be side-by-side vortex pairs spanning the channel cross section, as shown in Fig.…”
Section: A Helical Structure Of Instability Vortexmentioning
confidence: 82%
See 2 more Smart Citations
“…Upon a tangential electric field, these charges produce a Coulomb force and cause a movement of the liquid; experimental evidence for an electroosmotic flow at the liquid-liquid interface and in the liquid bulk is given in [2]. In spite of almost zero Reynolds numbers (negligible inertia effects), the electrohydrodynamics of liquid flows at micro-and nanoscales includes complicated instabilities [3] and bifurcations [4], and even chaotic motion at micro-and nanoscales, which is named as microturbulence.…”
Section: Introductionmentioning
confidence: 99%